2021
DOI: 10.1136/bmjpo-2020-000939
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in children: impact on child health

Abstract: Bullying in childhood is a major public health problem that increases the risk of poor health, social and educational outcomes in childhood and adolescence. These consequences are felt by all those involved in bullying (bullies, victims and bully–victims) and are now recognised to propagate deep into adulthood. Cyberbullying is a relatively new type of bullying in addition to the traditional forms of direct physical, direct verbal and indirect bullying. Children who are perceived as being ‘different’ in any wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(140 citation statements)
references
References 42 publications
1
66
0
8
Order By: Relevance
“…Socioeconomic status (SES) was assessed using the HBSC Family Affluence Scale (FAS III), which includes six items that measure material assets in the home, such as number of vehicles, bedroom sharing, computer ownership, bathrooms at home, dishwashers at home, and family vacations [39,40]. The item scores were summed with a score from 0 to 13 and categorized into three SES groups: low (0-5), average (6)(7)(8)(9) and high (10)(11)(12)(13). In the correlation analyses family affluence (FA) variable was used as continuous variable.…”
Section: Family Structure and Socioeconomic Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Socioeconomic status (SES) was assessed using the HBSC Family Affluence Scale (FAS III), which includes six items that measure material assets in the home, such as number of vehicles, bedroom sharing, computer ownership, bathrooms at home, dishwashers at home, and family vacations [39,40]. The item scores were summed with a score from 0 to 13 and categorized into three SES groups: low (0-5), average (6)(7)(8)(9) and high (10)(11)(12)(13). In the correlation analyses family affluence (FA) variable was used as continuous variable.…”
Section: Family Structure and Socioeconomic Statusmentioning
confidence: 99%
“…However, the peer interpersonal violence and cyberviolence involves not only bullies and victims, but also bully-victims, who both bully and are bullied by others [10,11]. It appears that adverse mental health outcomes due to bullying in adolescence most severely impact on bully-victims [12]. These studies explore the factors that contribute to the involvement of youth in cyberbullying by distinguishing them according to four categories of involvement: victims, bullies, bully-victims, and not involved.…”
Section: Introductionmentioning
confidence: 99%
“…School bullying is recognized as a global public health concern (UNESCO, 2019), with an adverse impact on the well-being and the psychological health of children and adolescents (Armitage, 2021;Klomek et al, 2015). Thus, it is a potential threat to children's rights, such as the right to learn and develop within a safe environment (Hymel et al, 2010;Rigby, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent associated health manifestations, was easily and rapidly angered (17.8%), scared to go to school (13%), unexplained bruises, and scratches (11%). (7) The impact of bullying on educational outcomes was summarized in a review done by Richard Armitage, in 2021 (8) . It is reported that the percentage of children frequently bullied compared with not frequently bullied, for the educational outcome; feeling like an outsider (left out of things at school) was 42.4% versus 14, 9% respectively.…”
mentioning
confidence: 99%
“…Also, feeling anxious for a test even if well prepared, was 63.9 % versus 54.6%, for the educational outcome, skipped school at least 3-4 days in the previous 2 weeks, was 9.2% versus 4.1%. (8) The (9) Although there are several effective national responses to reduce, or maintain low level of bullying in children, including political leadership, and commitment, training and support of teachers taking care of bullied children, and others (2) , there is no clear management, and referral pathways for health professionals dealing with childhood bullying, in both primary, and secondary care . (8)…”
mentioning
confidence: 99%